Стиль Руководства Президента Индонезии В Решении Национальных Проблем (Indonesian President's Style of Leadership in Addressing National Problems) - Suraya, Rahmat Syahid (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2023)
The study examines the leadership style and political landscape of seven Indonesian presidents. From President Sukarno to President Joko Widodo. The method used in this research is a qualitative research method with a literarure approach. This study uses the Northouse theory (2016), which describes 15 styles of leadership: character approach, skill approach, behavioral approach, situation approach, pathway theory, theory of exchange of leaders-members, transformational leadership, authentic Leadership, Servant Leadership; adaptive Leadership: psychodynamic approach; leadership ethics; team leadership; gender and leadership. The findings of this study show that the leadership styles of the seven Indonesian presidents differ from each other. President Sukarno is associated with the Character Approach, President Suharto with the Path-Goal Theory, President BJ Habibie with the Behavioral Approaching, President Abdurahman Wahid with the Skill Approximation, President Megawati Soakarno Princess with Gender and Leadership, and President Joko Widodo with the Servant-style Leadership Approche.